La legitimidad del estado moderno en la filosofía del derecho de Jurger Habermas (2012)
The present work takes the theoretical analysis as a purpose of one of the central categories of the modernity, since it is the case of the legitimacy of the Modern State, for it it is indispensable to come to the historical sources of the biggest thinkers as the so called classic ones of the European contractualismos (Thomas Hobbes, John Locke, Jean Jacques Rousseau and Immanuel Kant). Nevertheless, it is necessary to land the above mentioned study in the position of the most representative German philosopher of last times after Kant, Heidegger.I refer with it, to Jurger Habermas the most notable exponent of a metateórica of the legitimacy across the study of the theories of the legitimacy of the Modern State. The above mentioned assignment it fulfilsHabermas like a neo-legitimacy of the Modern State, from the proposition of five categories of Law of the juridical forms in the light of the beginning of speech, developed in the bottom in his theory of the communicative action and develado with major rigor in his philosophy of the right written in his work " Facticidad and Validity".